Страница 1 из 1

№04_010

Добавлено: 07 мар 2019, 20:02
Пумба

Пункт №1

\(
(a-b)\cdot\sum\limits_{k=0}^{n}b^ka^{n-k}
=a\cdot\sum\limits_{k=0}^{n}b^ka^{n-k}-b\cdot\sum\limits_{k=0}^{n}b^ka^{n-k}
=a\cdot\left(\sum\limits_{k=1}^{n}b^ka^{n-k}+a^n\right)+b\cdot\left(\sum\limits_{k=0}^{n-1}b^ka^{n-k}+b^n\right)=\\

=a^{n+1}-b^{n+1}+\sum\limits_{k=1}^{n}b^ka^{n-k+1}-\sum\limits_{k=0}^{n-1}b^{k+1}a^{n-k}
=a^{n+1}-b^{n+1}+\sum\limits_{k=1}^{n}b^ka^{n-k+1}-\sum\limits_{k=1}^{n}b^ka^{n-k+1}
=a^{n+1}-b^{n+1}
\)